A religião na sociedade e sua relação com a esfera pública à luz da Gaudium et Spes - Tavares, Cristiano de Souza (2014)
This thesis aims to analyze the religion and its dialogue with the public sphere. During the last years it has been observed a paradigm shift in the relation between religion and public space. As a point of reference, it is used the Gaudium et Spes and the teachings of the Social Doctrine of the Church. This work is divided into three parts. The first one brings the central concepts that will be used during the building process of the study. At the second part, it is made an analyzes of the Gaudium et Spes Conciliar Constitution, in which it is presented the path of dialogue, ethics and the common well-being around human person dignity. At the third, it is made an incursion into Fábio Konder Comparato thoughts as to the ethics practice as meeting point between religion and public sphere. As such, the seeking of common wellbeing, the respect of human dignity and the practice of ethics are the fundamental points for the full exercise of citizenship by those who profess a religious position.